2005
DOI: 10.1007/s00066-005-1319-5
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of Tumor Cell Lines after Pretreatment with the EGFR Tyrosine Kinase Inhibitor ZD1839 (Iressa®)

Abstract: The sensitivity to ZD1839 correlated with the EGFR expression level, an inhibition of cell proliferation, and induction of apoptosis in the cell lines analyzed. A radiosensitizing effect of ZD1839 was associated with downregulation of EGFR mRNA expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…Moreover, a study by Dittmann and colleagues (49) suggested that EGFR translocates to the nucleus in response to radiation-induced DNA damage, and more importantly, the nuclear EGFR shuttling was shown to be involved in the DNA damage repair. Nonetheless, our findings support these and other reports that demonstrated that activation of EGFR enhances overall DSB repair (33)(34)(35).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, a study by Dittmann and colleagues (49) suggested that EGFR translocates to the nucleus in response to radiation-induced DNA damage, and more importantly, the nuclear EGFR shuttling was shown to be involved in the DNA damage repair. Nonetheless, our findings support these and other reports that demonstrated that activation of EGFR enhances overall DSB repair (33)(34)(35).…”
Section: Discussionsupporting
confidence: 93%
“…(31) Moreover, EGFR inhibition was shown to induce cellular senescence in response to radiation and this was attributed to an increase in the levels of nonrepairable DSBs (32), suggesting a link between the EGF:EGFR pathway and the process of DNA damage repair. Finally, a previous study has demonstrated that in tumor cells exposed to ionizing radiation, activation of EGFR by EGF enhances the DSB repair capacity, whereas inhibition of EGFR attenuates DSB rejoining (33)(34)(35).…”
Section: Monocytes Enhance Ddr Via Hb-egf Releasementioning
confidence: 91%
“…As importantly, APE1 also functions as a reduction-oxidation activators of several transcription factors thought to be important in carcinogenesis, such as activator protein (Fos/Jun), hypoxia-inducible factor 1, cAMP-responsive element binding protein, and p53 (14,15). Knockout mouse model showed that inactivation of APE1 protein induces embryonic lethality and highlights the importance of its function to the cells (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well-known differences in radioresponse between SCLC and NSCLC, great differences in response exist between NSCLCs with the same histology. Expression and activity of EGFR are important determinants of radioresponse in several neoplasias, including NSCLCs, and loss of function mutations in the EGFR or anti-EGFR therapy has been shown to sensitize tumor cells to radiation (17)(18)(19). The discovery of activating mutations in the EGFR raises important questions about the response of mutant EGFR NSCLC to ionizing radiation (IR).…”
Section: Introductionmentioning
confidence: 99%